2013
DOI: 10.1080/13557858.2012.700917
|View full text |Cite
|
Sign up to set email alerts
|

The role of education for current, former and never-smoking among non-western immigrants in Norway. Does the pattern fit the model of the cigarette epidemic?

Abstract: Objectives. The aim was (1) to investigate the association between education and smoking status (current, former and never-smoking) among non-western immigrants in Norway and (2) examine if these associations fit the pattern predicted by the model of the cigarette epidemic.Design. Data came from the Oslo Health Study and the Oslo Immigrant Health study (2000–2002). The first included all Oslo citizens from seven selected birth cohorts. The second included all Oslo citizens born in Turkey, Iran, Pakistan, Vietn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
4
7
1
Order By: Relevance
“…In our study, almost all women neither drank any alcohol nor smoked, while few men drank, and the prevalence of current smoking (19%) is lower than that previously reported for other immigrant groups (31-45%). Moreover, while the proportion having low physical activity was high compared to other immigrant groups (Vedoy 2013), half of the participants in this study still reported walking more than 30 min per day.…”
Section: Discussioncontrasting
confidence: 52%
“…In our study, almost all women neither drank any alcohol nor smoked, while few men drank, and the prevalence of current smoking (19%) is lower than that previously reported for other immigrant groups (31-45%). Moreover, while the proportion having low physical activity was high compared to other immigrant groups (Vedoy 2013), half of the participants in this study still reported walking more than 30 min per day.…”
Section: Discussioncontrasting
confidence: 52%
“…Our findings regarding the larger proportion of daily smokers among Russian and Kurdish migrant men compared to the general population are in concordance with previous European studies and also with preliminary findings from the Maamu survey, reporting a larger proportion of daily smokers among migrants in comparison to the general population [12,18,20,21,[55][56][57], and in concordance with previous studies reporting differences between migrant groups under study [11,12,18,46,47,49,55,56,[58][59][60]. In contrast, previous migrant studies from Spain, Denmark and United States, have reported less smoking or similar smoking behaviour than the general population [15,16,50,60].…”
Section: Cigarette Smokingsupporting
confidence: 93%
“…In particular, diet may be healthier and the prevalence of obesity and alcohol consumption lower in immigrants than in some high‐income host populations before and immediately after arrival . On the other hand, self‐reported physical inactivity tend to be higher in immigrants compared to the host population in Norway, and smoking prevalence is very high in some immigrant groups …”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] On the other hand, self-reported physical inactivity tend to be higher in immigrants compared to the host population in Norway, 40 and smoking prevalence is very high in some immigrant groups. 41 After moving to the host country, immigrants go through various degrees of acculturation. Many factors, for example, socioeconomic status and occupation, can influence the acculturation process, 42 and affect cancer incidence.…”
Section: Cancer Epidemiologymentioning
confidence: 99%